Physical and biological characteristics of silver/ polyvinylpyrrolidone nanocomposite using pandanus atrocarpus - Jabbar, Abdullah Hasan (2021)
In the present study, synthesis and characterization of silver nanoparticle (AgNPs) and Polyvinylpyrrolidone (PVP) nanocomposite (PVP-AgNCs) and their biological applications were studied. AgNPs and PVP-AgNCs were synthesised by biological method using Pandanus atrocarpus extract (PAE) as a reducing agent. The detailed characterization of PAE-AgNPs and PVP-AgNPs was carried out using UltravioletVisible (UV-Vis), Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscope (FESEM) and X-Ray Diffraction (XRD). UV-Vis peak of PAE-AgNPs and PVP-AgNCs obtained at 432 nm and 540 nm respectively. FTIR's prominent peaks in PAE and AgNPs and PVP-AgNCs do not considerably differ from each other and are located at 3338, 2131, 1638, 1295, and 428. The prominent peak at 3338 belongs to the –OH group. FESEM confirmed the production of smallest PAE-AgNPs is of 14 nm in a spherical shape‘s range while smallest PVPAgNCs was 44 nm. The Bragg‘s reflection values of 38°, 44°, 64°, and 77° were obtained for PAE-AgNPs and PVP-AgNCs corresponding to the set of lattice planes (111), (200), (220) and (311) at 2θ. This indicates the formation of face centred cubic (fcc) crystalline structure of the nanostructure. The main findings include the biological activities of the PAE, PAE-AgNPs PVP-AgNCs as cytotoxicity, antioxidant, anti-enzymatic, and antiurolithitaic activities. Five different concentration of sample tested (100 µg/mL - 500 µg/mL), all the results were dose dependant. For cytotoxicity, as the concentration increases to 500 µg/mL, the mortality was about 16.7 % for PAE-AgNPs, while 23.3 % for PVP-AgNCs. The ABTS radical scavenging activity (% I) of PAE was recorded at 58.20 %, PAEAgNPs at 64.20 %, and PVP/AgNC at 76.00 % at concentration of 500 µg/mL. The absorbance values of PAE, PAE-AgNPs, and PVP-AgNC at 16 min in antiurolithiatic assay was recorded at 0.299, 0.291 and 0.299, respectively, which are significantly different (p < 0.05). Percent inhibition of anti-enzymatic activity of PAE, PAE-AgNPs and PVP-AgNC was 42.30%, 48.70%, and 54.40%, respectively. From our findings it is concluded that AgNPs, and PVP-AgNCs from Pandanus atrocarpus is safe and eco-friendly, and hence needs to be studied in vivo